2018
DOI: 10.1515/esp-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Retention in Electrospun Fibers Affects Scaffold Mechanical Properties

Abstract: Electrospinning is a robust material fabrication method allowing for fine control of mechanical, chemical, and functional properties in scaffold manufacturing. Electrospun fiber scaffolds have gained prominence for their potential in a variety of applications such as tissue engineering and textile manufacturing, yet none have assessed the impact of solvent retention in fibers on the scaffold’s mechanical properties. In this study, we hypothesized that retained electrospinning solvent acts as a plasticizer, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The solvents in this study had to be selected regarding electrospinnability. PET has been already electrospun from a trifluoroacetic acid (TFA), a mixture of TFA/DCM [ 44 , 66 , 67 ] in various portions or from HFIP and HFIP/DCM [ 33 , 68 ]. In the case of silk fibroin, it has been proven many times that the SF could be electrospun from aqueous solutions only with the aid of an auxiliary polymer [ 69 , 70 ]; however, it was successfully electrospun from formic acid (FA), TFA, and HFIP [ 58 , 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…The solvents in this study had to be selected regarding electrospinnability. PET has been already electrospun from a trifluoroacetic acid (TFA), a mixture of TFA/DCM [ 44 , 66 , 67 ] in various portions or from HFIP and HFIP/DCM [ 33 , 68 ]. In the case of silk fibroin, it has been proven many times that the SF could be electrospun from aqueous solutions only with the aid of an auxiliary polymer [ 69 , 70 ]; however, it was successfully electrospun from formic acid (FA), TFA, and HFIP [ 58 , 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that electrospun PGA fibers retained a higher amount of HFIP than that measured with electrospun PLC fibers [19]. HFIP is progressively removed from PLC fibers until complete evaporation, which is not the case for PGA electrospun fibers, where remaining solvent was still detected after 14 days [19]. Moreover, PCL has no significant interaction with HFIP (2,3), whereas PLLA has an affinity [20].…”
Section: Sample B)mentioning
confidence: 95%
“…Solvent retention is a critical property, due to the toxicity of the solvent used during electrospinning [19]. It was reported that electrospun PGA fibers retained a higher amount of HFIP than that measured with electrospun PLC fibers [19].…”
Section: Sample B)mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrospun nanofibers P(AN-MA) showed all the characteristic peaks of P(AN-MA), in particular the distinctive nitrile (C≡N) vibration at 2243 cm −1 and the CH2 bending vibration at 1454 cm −1 . The characteristic peaks at 1734 cm −1 (marked with a triangle) can be associated with the (C=O) stretching vibration of the methacrylic acid functional groups [34]. We investigated to which extent sterilization would affect the P(AN-MA) nanofibers, since sterilization may alter the properties of electrospun nanofibers [35].…”
Section: Characterization Of the Nanofiber Matsmentioning
confidence: 99%